Penggunaan Media Pembelajaran Origami terhadap Hasil Belajar Matematika Siswa Kelas V Sekolah Dasar - Yeni Purnamasari; Samrin Samrin; Muh. Syarwa Sangila (IAIN Kendari, 2022)
This study aims to improve students' mathematics learning abilities through the use of origami learning media in fifth grade mathematics learning. This study is a classroom action research. The subjects of this research were the fifth grade students of SD Negeri 7 Lasolo, which consisted of 13 students. Data collection techniques used observation, tests, and documentation. Data analysis was in the form of quantitative and qualitative descriptive. The results of the study show that the use of folding paper (origami) learning media can improve students' mathematics learning outcomes. The completeness of student learning outcomes in the pre-cycle was 38.46%, with an average value of 57.69. After the first cycle of action there was an increase in student learning outcomes with a percentage of 61.53% and an average value of 66.92. In this second cycle, student learning outcomes increased with a percentage of 76.92% and an average value of 72.61. Increasing student learning outcomes from pre-action to cycle II was 25.86%.Keywords: Origami, mathematic learning outcome, geometry